High speed solution-processed hybrid perovskite photodetectors with low dark current enabled by a low temperature metal oxide interlayer. (30th July 2018) - Perini, Carlo A R; Barker, Alex J; Sala, Matteo; Petrozza, Annamaria; Caironi, Mario
Abstract: Metal halide perovskites are very promising for the realization of high performance, solution-processed photodetectors, paving the way to cost-effective manufacturing of optoelectronics systems. However, most of the high speed, high-detectivity perovskite photodiodes reported so far include evaporated interlayers in the device stack in order to limit dark currents. Here we adopt a solution-processed aluminum doped-ZnO film as n-type charge selective interlayer, within a fully solution-processed stack comprising a polymer p-type interlayer and a metal halide perovskite photoactive layer. As a result, dark current values are limited to 1.4 × 10 −7 A cm −2 at −1 V, and responsivity exceeds 0.1 A W −1 in the visible range, corresponding to an external quantum efficiency exceeding 35%. At the same time, the good conductivity of the metal oxide allows for high operational speeds, providing a decay time as low as 100 ns, an order of magnitude lower than what typically achieved with solution-processed organic interlayers. Such response corresponds to a −3 dB bandwidth of 3.5 MHz.